STEADY-STATE DISSOLUTION KINETICS OF GOETHITE IN THE PRESENCE OF DESFERRIOXAMINE B AND OXALATE LIGANDS: IMPLICATIONS FOR THE MICROBIAL ACQUISITION OF IRON - Cheah S.-F.; Cervini-Silva J.; Sposito G.; Kraemer S.M. (My University, 2003)
This paper reports an investigation of the effects of a trihydroxamate siderophore, desferrioxamine B (DFO-B), and a common biological ligand, oxalate, on the steady-state dissolution of goethite at pH 5 and 25 °C. The main goal of our study was to quantify the adsorption of the ligands and the dissolution of goethite they promote in a two-ligand system. In systems with one ligand only, the adsorption of oxalate and DFO-B each followed an L-type isotherm. The surface excess of oxalate was approximately 40 mmol kg−1 at solution concentrations above 80 μM, whereas the surface excess of DFO-B was only 1.2 mmol kg−1 at 80 μM solution concentration. In the two-ligand systems, oxalate decreased DFO-B adsorption quite significantly, but not vice versa. For example, in solutions containing 40 μM DFO-B and 40 μM oxalate, 30% of the DFO-B adsorbed in the absence of oxalate was displaced. The mass-normalized dissolution rate of goethite in the presence of DFO-B alone increased as the surface excess of the ligand increased, suggesting a ligand-promoted dissolution mechanism. In systems containing oxalate only, mass-normalized goethite dissolution rates were very low at concentrations below 200 μM, despite maximal adsorption of the ligand. At higher oxalate concentrations (up to 8 mM), the steady-state dissolution rate continued to increase, even though the surface excess of adsorbed ligand was essentially constant. Chemical affinity calculations and dissolution experiments with variation of the reactor flow rate showed that far-from-equilibrium conditions did not obtain in systems containing oxalate at concentrations below 5 mM. The dissolution rate in the presence of DFO-B at solution concentrations between 1 and 80 μM was approximately doubled when oxalate was also present at 40 μM solution concentration. The dissolution rate in the presence of oxalate at solution concentrations between 0 and 200 μM was increased by more than an order of magnitude when DFO-B was also present at 40 μM solution concentration. Chemical affinity calculations showed that, in systems containing DFO-B, goethite dissolution was always under far-from-equilibrium conditions, irrespective of the presence of oxalate. These results were described quantitatively by a model rate law containing a term proportional to the surface excess of DFO-B and a term proportional to that of oxalate, with both surface excesses being determined in the two-ligand system. The pseudo first-order rate coefficient in the DFO-B term has the same value as measured for goethite dissolution in the presence of DFO-B only, while the rate coefficient in the oxalate term must be measured in the two-ligand system, since it is only in this system that far-from-equilibrium conditions obtain. These latter conditions do not exist in the system containing oxalate only, but they do exist in the DFO-B/oxalate system because the siderophore is able to remove Fe(III) from all Fe–oxalate complexes rapidly, leaving the uncomplexed oxalate ligand in solution free to react again with the goethite surface. This synergy observed in the two-ligand system implies that the production of modest quantities of siderophore in the presence of very low concentrations of oxalate would be an extremely effective mechanism for the microbially induced release of Fe from goethite.